Breaking dawn [compact disc, unabridged] - Meyer, Stephenie, 1973- (Meyer, Stephenie, 1973- Twilight saga, 2008)
Pulled in one direction by her intense passion for vampire Edward Cullen, and in another by her profound connection with werewolf Jacob Black, Ellen Swan has endured a tumultuous year of temptation, loss, and strife to reach the utimate turning point. She must choose to either join the dark but seductive world of immortals or pursue a fully human life. This is the thread from which the fate of two tribes hangs.